The case of the counterfeit criminals - Stratford, Jordan (Stratford, Jordan. Wollstonecraft Detective Agency, 2017)
When a dinosaur fossil hunter is blackmailed by kidnappers who need her to fake a validation in return of her beloved pooch, Ada and Mary are given three days to find the offenders and save the scientist's reputation.